Student and Parent Perspectives of the Transition From Primary to Secondary School for Students With Autism Spectrum Disorder - Stack, Karen; Symonds, Jennifer E.; Kinsella, William (Frontiers in Education, 2020)
Title: Student and Parental Perspectives of the Transition from Primary to Secondary School for Students with Autism Spectrum Disorder Objective: Transition from primary school to secondary school is an important point in a young person’s development. Children’s experiences at transition have been found to have an enduring impact on their social and academic performance and potentially their success or failure at secondary school. This primary-secondary transition frequently presents challenges for children with Autism Spectrum Disorder (ASD), resulting in uncertainty and anxiety. The objective of this study was to explore the perceptions of children with ASD, on the topic of which features of school environment fit more or less well with their needs, as they transferred from primary to secondary schools. Method: Semi-structured interviews were used to gather the experiences of 6 students with ASD, and their parents, before and after the transition to secondary school. A thematic analysis of these data identified common themes that captured the fits and misfits between the children’s needs and their primary and secondary school environments. Result: Overall, participants voiced more positive perspectives of secondary school than primary school. Data analysis identified themes of; feelings about school; peer relationships, relationship with school staff, curriculum, school organisation and accommodations. Conclusion: Inclusion and integration of students with ASD in mainstream secondary school at transition can be a positive experience when the individual needs of each child with ASD are considered to fit with the secondary school environment. The transition can present more challenges for students where a one size fits all approach is taken.